THE SEMANTIC ANALYSIS OF THE ENGLISH CULTURAL KEY WORD “RIGHT” AND ITS EQUIVALENTS IN ITALIAN - Moisejeva, Natalija (Vertimo studijos, 2017)
The present research paper aims at providing an insight into the nature of the English cultural key word right and its expression in Italian. The analysis carried out during the research is based on the theory of Cultural Key Words elaborated by Anna Wierzbicka and Cliff Goddard in the 1990s, who claimed that apart from common words which are clear to everyone, there exist certain culture-specific concepts which are fully understandable only to members of a specific culture. The main attention of this article, therefore, is focused on revealing the meaning groups of the concept right and their expression in Italian. The source of the data is the original version of George Orwell’s 1984 and its Italian translation. Preliminary results show that the cultural concept right is manifold and mostly used to refer to instances from the meaning groups of precision, correctness and well-being. This analysis also suggests that the concept right is indeed specific to English culture since Italian culture employs different lexical means in order to convey the ideas underlying this concept.